Applied evolutionary economics and economic geography - European Meeting on Applied Evolutionary Economics 2005 : Utrecht, Netherlands); Frenken, Koen, 1972- (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2007)
"The volume Applied Evolutionary Economics and Economic Geography, the fourth book published by Edward Elgar on applied evolutionary economics stems from the fourth European Meeting on Applied Evolutionary Economics (EMAEE) held in Utrecht, 19-21 May, 2005. ... The present volume aims to advance empirical methodologies in evolutionary economics, this time with a special emphasis on geography"-- Preface.
Includes bibliographical references and index.
lje 29/04/13
Loan
Keywords: Evolutionary economics -- Congresses; Economic geography -- Congresses